We Are (Not) Who We Were: Irish Cultural Nationalism and the Battle Over Tara - (:unkn) unknown (My University, 2015)
This paper traces the controversy over the construction of a major motorway through the heart of one of Ireland’s most iconic and treasured heritage sites: The Hill of Tara. Through qualitative content analysis of opponents’ discursive strategies, the author reveals how key nationalistic themes that have been repeatedly utilized by Irish political actors during historical episodes of contention and state-building are reactivated within this contemporary political struggle. This is a theoretically compelling exercise because it reveals the durability of nationalist symbols over time and in diverse political contexts. In the case of Ireland, it demonstrates how citizens make sense of themselves in terms of their past and how culturally significant spaces play a central role in the process of national identity construction in this relatively young republic. It also provides insight into the strategic aspect of identity formation as it is linked to frame alignment processes in a manifestly inter-connected and globalizing world. In the case of Tara, this process is complicated by conflicting pressures of modernity and the allure of economic prosperity that also vie for pre-eminence as national interests.
Keywords: Ireland; Cultural Nationalism; Globalization; Heritage Sites